Nanoparticulate carriers (NPC) for oral pharmaceutics and nutraceutics - Lopes, Carla Martins (2020)
The introduction of nanoparticulate carriers (NPC) in the pharmaceutic and nutraceutic fields has changed the definitions of disease management and treatment, diagnosis, as well as the supply food chain in the agri-food sector. NPC composed of synthetic polymers, proteins or polysaccharides gather interesting properties to be used for oral administration of pharmaceutics and nutraceutics. Oral administration remains the most convenient way of delivering drugs (e.g. peptides, proteins and nucleic acids) since these suffer similar metabolic pathways as food supply. Recent advances in biotechnology have produced highly potent new molecules however with low oral bioavailability. A suitable and promising approach to overcome their sensitivity to chemical and enzymatic hydrolysis as well as the poor cellular uptake, would be their entrapment within suitable gastrointestinal (GI) resistant NPC. Increasing attention has been paid to the potential use of NPC for peptides, proteins, antioxidants (carotenoids, omega fatty acids, coenzyme Q10), vitamins, probiotics, for oral administration. This review focuses on the most important materials to produce NPC for oral administration, and the most recent achievements in the production techniques and bioactives successfully delivered by these means.